MODERN METHODS OF DIAGNOSING BACTERIAL INFECTIONS - Begimkulova Nigina (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Bacterial infections are one of the leading causes of morbidity and mortality worldwide. According to the World Health Organization, more than 700 million cases of bacterial infections are reported annually, with more than 6 million deaths associated with complications from bacterial diseases [1, 2]. Among the most significant pathogens are Staphylococcus aureus, Escherichia coli, Klebsiella pneumoniae, and Pseudomonas aeruginosa, which cause both hospital-acquired and community-acquired infections. Modern medicine faces several key challenges in the field of bacterial infections. First, there is the rise of antibiotic resistance, when conventional treatment regimens become ineffective. For example, the spread of methicillin-resistant strains of S. aureus (MRSA) and extended-spectrum beta-lactamase (ESBL) producers significantly complicates treatment and increases the risk of fatal outcomes [3, 4]. Second, early detection of infections is becoming critically important for preventing serious complications such as sepsis, tissue necrosis, and multiple organ failure.